Extreme events and conservation of subtidal habitats: Effects of a rainfall flood on coralligenous reefs. (April 2021) - Piazzi, L.; Cecchi, E.; Cinti, M.F.; Ceccherelli, G.
Abstract: The increase of the intensity and frequency of rainfall-dominated flood is considered a main effect of climate change. The present study evaluated the effect of a rainfall flood event on coralligenous reefs. The flooded site was compared to three control sites using a Before/After-Control/Impact (BACI) design. Sites were sampled using the STAR (STAndaRdized coralligenous evaluation procedure) approach and three ecological indices (ESCA, COARSE and ISLA) were calculated. At the disturbed site the number of species per sample, beta diversity, sensitivity levels of assemblages and the values of the three indices were lower after the flooding event, while the same variables did not decrease at the control sites. Algal turf and Dictyotales increased at the disturbed sites after the flood event, while Udoteaceae, erect sponges, bryozoans and Corallium rubrum decreased. This study provides evidence for identifying floods as a further cause of degradation for the coralligenous reef assemblages. Highlights: The study evaluated the effect of a rainfall flood event on coralligenous reefs. A flooded site was compared to three control sites using a BACI design. Sites were sampled using the STAndaRdized coralligenous evaluation procedure approach. At the flooded site, both diversity and ecological quality decreased. At the flooded site, Udoteaceae, sponges, bryozoans and Corallium rubrum decreased.